Penyuluhan Dan Pelatihan Tanggap Darurat Kebakaran Pada Rumah Tangga Di Kelurahan Sukorame, Mojoroto, Kediri - Rahma, Naufa Aulia; Widodo, Silvi Rushanti; Triparianto, Afiff Yudha; Safi'i, Imam; Indrasari, Lolyka Dewi; Komari, Ana; A. Rahim, Muslimin; Ramadhani, Rosyidina Maula; Jun, David (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
The most important cause of fires in the residential environment is the human error factor. In Kediri, East Java, throughout 2024, there have been 8 incidents of spread reported and published on the Kediri news page. Some of these incidents were caused by gas stoves. Therefore, it is necessary to have counseling activities and firefighting practices for the community to improve people's skills and knowledge about fires caused by gas stoves. This activity is in the form of an introduction to the basics of fire, such as the types of fires and their extinguishers, as well as fire extinguishing training. This activity was carried out and aimed at the residents of Sukorame Village, Mojoroto, Kediri. In providing information to the community, several community empowerment activities will be carried out, including the following: 1. Introducing the basics of fire and fire safety to the community of Sukorame Village, Kediri, 2. Conducting practical counseling on how to use fire extinguishers properly and correctly, 3. Assisting by providing a user manual in the form of a booklet. From the results of community service, the results found that previously, people were still unfamiliar with portable fire extinguishers (APAR) to better understand the importance of the availability of fire extinguishers at home. The community also became more aware of how to extinguish fires using fire extinguishers and using wet fabric or burlap sacks